Perspectiva de género y empoderamiento de la mujer durante la Primera Infancia en Colombia en los últimos diez años (2020)
Colombia is one of the countries in Latin America with a patriarchal culture that affects women and girls because of the expressions of gender violence and the inequalities that occur without discrimination of age or social stratum. There are still manifestations of discrimination against women and the gaps of inequality in the economy, politics and education are a constant in the country; the data show that there is progress in Colombia, but it has been slow, insufficient and unequal. Unfortunately, cases of gender-based violence are increasing every day, or we could say that they are more easily made visible by the media. Every 28 minutes a woman is a victim of gender violence in Colombia according to a report by the Free University's law faculty and this data is partial since only one out of every three cases of abuse is reported. Government agencies are being inundated with lawsuits involving the violation of women's rights, including those of minors. Colombian law has not yet been forceful in modifying and applying the legislature to ensure compliance with the rights of women and girls, especially when the cases exceed the statistics and the State does not correctly administer the existing tools for the protection of the violated population.